The utility of psychiatric diagnosis: Diagnostic classifications in clinical practice and research in relation to eating disorders - Telléus, Gry Kjærsdam (Academic Quarter | Akademisk kvarter, 2016)
The validity of psychiatric diagnoses has been challenged because of a generally low validity of the existing diagnostic categories. However, it is important to distinguish between the validity and the utility of the psychiatric diagnostics. Although the validity of most contemporary psychiatric diagnoses is generally low and characterized by a low degree of natural boundaries, this does not mean that most psychiatric diagnoses are not useful concepts. The aim of this article is to focus on the utility of psychiatric diagnoses. This utility will be demonstrated with eating disorders as an example.